Calorie-restricted diet mitigates weight gain and metabolic abnormalities in obese women with schizophrenia: a randomized controlled trial - Zhang, Lei; Zhu, Mingwen; Liu, Xiangqun; Zhao, Zhijun; Han, Ping; Lv, Luxian; Yang, Chun; Han, Yong (Frontiers in Nutrition, 2023)
Background Obesity is a prevalent health problem in patients with schizophrenia, and calorie restriction diet (CRD) achieved effective weight loss and metabolic improvement; however, these have not been rigorously evaluated in obese patients with schizophrenia. Objective To measure the effects of CRD on weight loss and metabolic status in hospitalized obese women with schizophrenia during a 4-week period. Methods Participants were randomly assigned to two groups in a 1:1 ratio. The intervention group (n = 47) was asked to follow a CRD and the control group (n = 48) a normal diet for 4 weeks. Outcomes of body weight, body composition, as well as metabolic parameters were measured at baseline and following the intervention period. Results Forty-five participants completed the 4-week research in both the intervention and control groups. Compared to the normal diet, adherence to the CRD significantly decreased body weight (2.38 ± 1.30 kg), body mass index (0.94 ± 0.52 kg/m2), waist circumference (4.34 ± 2.75 cm), hip circumference (3.37 ± 2.36 cm), mid-upper circumferences, triceps skin-fold thickness, fat mass and free fat mass with large effect sizes (p = <0.001, ηp2 range between 0.145 and 0.571), as well as total cholesterol (0.69 ± 0.70 mmol/L) with a medium effect size (p = 0.028, ηp2 = 0.054). There were no differences between the CRD and control groups in terms of pre-post changes in triglycerides, high- and low-density lipoprotein-cholesterols, as well as systolic and diastolic blood pressures (p > 0.05). Conclusion CRD is preventative of weight gain, but not apparent in intervention for metabolic status in hospitalized obese women with schizophrenia. Clinical trial registration: http://www.chictr.org.cn, ChiCTR-INR-16009185.